Efficacy of methods to synchronize follicular wave emergence in pregnant heifers - Cameron B. Hayden; Jessica C.L. Motta; Rodrigo V. Sala; Nora M. Bello; Marco A. Coutinho da Silva; Alvaro García-Guerra (JDS Communications)
The objective of the present study was to evaluate the efficacy of various methods for synchronization of follicular wave emergence (FWE) in pregnant heifers. Pregnant (60 d of gestation) Holstein heifers (n = 86) arranged in cohorts were randomly assigned to be administered 172 µg of gonadorelin acetate (GnRH), 3,300 IU of human chorionic gonadotropin (hCG), follicular ablation of follicles >5 mm (FA), or saline (control). Ultrasonography was performed to determine ovulation and emergence of a new follicular wave. Data were analyzed using generalized linear mixed models with treatment as a fixed effect and cohort as a random effect. Ovulatory response was greater for hCG (81.0%; 95% CI: 58.0–92.9) than GnRH-treated (50.0%; 95% CI: 28.8–71.2) heifers, whereas ovulation was not observed for heifers in the FA or control groups. Heifers in the FA group had a shorter (34.8 ± 1.7 h) interval from treatment to FWE compared with heifers in the hCG (51.8 ± 5.3 h), GnRH (56.8 ± 5.3 h), and control (61.4 ± 9.8 h) groups. Furthermore, treatments differed in variability of time to FWE, whereby FA-treated heifers had less variable, more consistent responses than hCG and GnRH heifers. These groups were, in turn, less variable in time to FWE than heifers in the control group. Synchronization of FWE efficacy was greater in FA (97.6%; 95% CI: 69.8%–99.9%) and hCG-treated (75.0%; 95% CI: 52.8%–89.0%) heifers than control (27.5%; 95% CI: 12.2%–50.9%) heifers, with marginal evidence for a difference between GnRH (69.1%; 95% CI: 46.4%–85.2%) and control heifers. Overall, we found no evidence for differences in FWE synchronization efficacy between hCG, GnRH, and FA. Nevertheless, FA resulted in a shorter and less variable interval from treatment to FWE, thus providing a more precise control of follicular development.